Challenges and Opportunities in Performance Management for MSMEs Keluar Kemana (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This research aims to analyze the challenges and opportunities in the implementation of performance management at MSMEs Keluar Kemana in Tanjungpinang, Riau Islands. The focus of the research includes operational management, service quality, financial management, and human resource development to improve competitiveness and business sustainability. This research uses a qualitative method with a case study approach. Data collection techniques include interviews with business owners, direct observation at the location, and analysis of documentation such as financial reports and operational records. The type of sample used in the study was purposive sampling with the informant of the owner of the UMKM Keluar Kemana, Fazira Rahmadani. The data was analyzed descriptively qualitatively, where information was classified and interpreted to get a comprehensive picture. The research results of this study are that the challenges faced are such as consistency in product quality, financial management, fierce competition and employee motivation, but great opportunities are seen through digitization of promotions, business expansion, HR development, service improvement, and technology-based financial management for growth.